Determination of the Engineering Properties of Submarine Soil Layers in the Bohai Sea Using the Piezocone Penetration Test - Bohong Wu; Guihe Wang; Jiong Li; Yu Wang; Baolin Liu (Advances in Civil Engineering)
Due to the complexity of marine geotechnical engineering, the harsh operating environments, loose subsea soils, and high water contents, it is extremely difficult to obtain soil samples while maintaining the in situ conditions in offshore areas. The engineering properties of submarine soil layers in the Bohai Sea, China, were investigated in this work. The Wison-APB borehole wireline piezocone penetration test (CPTU) system was used to conduct direct measurements of the cone tip resistance, sleeve friction, and pore pressure. The soil classification and the related soil properties, such as the undrained shear strength, sensitivity and overconsolidation ratio, shear strength profile at the investigation depths, and the single pile foundation bearing capacity, were estimated. Laboratory tests were also conducted in this work. The CPT test results show that there were large differences between the results of the CPT tests (Su) and the laboratory experimental results, which may be due to the compact silt and hard clay interbeds in some layers. The soil classification was determined according to the previous literature. The laboratory test results of the undrained shear strength, clay sensitivity, and the OCR match the CPT test results best when the parameters Nkt, Ns, and k are 15, 6, and 0.3, respectively. The final determination of the ultimate pile capacity depends on the soil’s mechanical properties and the pile type and design. The effects of wave surge and wind loading should also be taken into account in offshore engineering.